Beetles of Eastern North America - Evans, Arthur V. (Book collections on Project MUSE., 2014)
A comprehensive full-color guide to the remarkably diverse and beautiful beetles of the United States and Canada east of the Mississippi River. It is the first color-illustrated guide to cover 1,406 species in all 115 families that occur in the region - and the first new in-depth guide to the region in more that forty years. Lavishly illustrated with over 1,500 stunning color images by some of the best insect photographers in North America, the book features an engaging and authoritative text by noted beetle expert Arthur Evans.